Economic-injury level of Empoasca kraemeri on Vigna unguiculata - Moraes, Gilberto J. de; Sardana, Brushan; Oliveira, Carlos A.V. (Pesquisa Agropecuaria Brasileira, 2014)
The economic-injury level of E. kraemeri on V. unguiculata was studied under field conditions in Petrolina, Pernambuco, State, Brazil. In this study, the percentage reduction in productivity was correlated with the average infestation level of E. kraemeri within 20 to 60 days after planting period. From such correlation, the following equations were deduced to calculate the economic-injury level for varieties Pitiúba and Sempre Verde: E.I.L. = 5,226(control cost/kg/Product. without attack kg/ha x Cost of bean/ka) 1.677 and E.I.L. = 2,76 (Control cost/kg/Product. without attack kg/ha x Cost of bean/kg) 1.517, respectively.
Keywords: Pitiúba; Sempre Verde